Rukun Iman Sebagai Dasar Pengelolaan Keuangan Daerah - Dinda Pramudita Jiwandono; Vety Munawaroh; Mohamad Djasuli (Shafin: Sharia Finance and Accounting Journal, 2023)
Regional financial management can be carried out economically, efficiently, effectively. By being associated with the pillars of faith to produce accountable and transparent financial management. Local governments must also be able to manage their regional finances to improve and develop people's welfare by carrying out good management. Regional finances are managed in accordance with applicable regulations, managed efficiently, effectively, accountably, transparently, economically and responsibly. The research method used by the author is a qualitative descriptive method, which describes the data collected and analyzed. The subject of this research is the regional finance section, with the object of pillars of faith as the basis for its management. The data source used is secondary data obtained from literature, previous research journals, such as books, magazines, and company document data needed. The results of this study explain that through management of the pillars of faith finance, everyone has responsibility for the actions that have been done in the world, will return to himself. If this principle is believed, it will have a major influence on regional financial management. Everyone will try to do good and be afraid of doing bad, and when he does bad he will immediately repent and realize all his mistakes